HYBRID SOLAR-BIOMASS SYSTEMS FOR OFF-GRID RURAL ELECTRIFICATION: TECHNO-ECONOMIC AND ENVIRONMENTAL ASSESSMENT - Ardi Azhar Nampira; Felipe Souza; Rafaela Lima (Journal of Moeslim Research Technik, 2025)
This study investigates the potential of a hybrid solar-biomass system to provide reliable and sustainable electricity to off-grid rural communities. The research background highlights the critical energy poverty prevalent in many rural areas, which lacks access to a stable power grid. While solar energy is a promising solution, its intermittent nature often limits its reliability. The primary objective is to conduct a comprehensive techno-economic and environmental assessment of a hybrid solar-biomass system. The study aims to design an optimized system configuration that can meet the energy demand of a typical rural village while minimizing the levelized cost of energy (LCOE) and reducing the system’s overall carbon footprint. The research seeks to demonstrate a viable and sustainable alternative to conventional fossil fuel-based generation. The research methodology involves creating a detailed energy model of a hybrid system using specialized software. The model integrates solar photovoltaic (PV) panels, a biomass gasifier, and a battery storage system.. The research findings demonstrate that the hybrid system is a technically and economically feasible solution for rural electrification. The optimized configuration achieved a low LCOE of $0.25/kWh, which is competitive with diesel-based generators. The environmental assessment projected a 75% reduction in GHG emissions. The conclusion is that hybrid solar-biomass systems provide a highly effective, cost-efficient, and environmentally sound approach to off-grid rural electrification. to both economic development and climate change mitigation goals.